The design of a professional career ladder for teachers: do extrinsic incentives trigger intrinsic motivation for improving teaching - the case of Chile - Miguel Órdenes; Deborah Ulloa (Taylor & Francis Group, 2024)
This study explores the linkages between extrinsic and intrinsic motivation in teachers who are regulated by a career ladder policy in Chile. This work pays attention to specific components of this policy: salary increase, promotion, standards, performance evaluation, and feedback. We shed light on the motivational pattern that emerges from teachers' experience with this policy design. Drawing on work motivation literature and the 'contingent performance' model, the study theorizes that perceived competence links extrinsic policy elements to educators' intrinsic concerns for teaching quality. Using a qualitative approach and exploring in 24 teachers' semi-structured interviews, the article tests and validates the theoretical model. Findings uncovered two distinct groups of educators: one group that connects promotion and performance evaluation with their intrinsic concern of instructional quality and another group who did not. The perception of competence or 'competence cueing' as a connection between extrinsic and intrinsic motivation was an essential factor to distinguish between the two groups. Modest evaluative threat, attributed validity of the evaluation system, and usefulness of the process seem to be enabling conditions for teachers to recognize the career ladder as a system that speaks to their sense of competence.